let X be non empty set ; :: thesis: for S being SigmaField of X
for f being with_the_same_dom Functional_Sequence of X,COMPLEX
for g being PartFunc of X,COMPLEX
for E being Element of S st dom (f . 0) = E & ( for n being Nat holds f . n is E -measurable ) & dom g = E & ( for x being Element of X st x in E holds
( f # x is convergent & g . x = lim (f # x) ) ) holds
g is E -measurable

let S be SigmaField of X; :: thesis: for f being with_the_same_dom Functional_Sequence of X,COMPLEX
for g being PartFunc of X,COMPLEX
for E being Element of S st dom (f . 0) = E & ( for n being Nat holds f . n is E -measurable ) & dom g = E & ( for x being Element of X st x in E holds
( f # x is convergent & g . x = lim (f # x) ) ) holds
g is E -measurable

let f be with_the_same_dom Functional_Sequence of X,COMPLEX; :: thesis: for g being PartFunc of X,COMPLEX
for E being Element of S st dom (f . 0) = E & ( for n being Nat holds f . n is E -measurable ) & dom g = E & ( for x being Element of X st x in E holds
( f # x is convergent & g . x = lim (f # x) ) ) holds
g is E -measurable

let g be PartFunc of X,COMPLEX; :: thesis: for E being Element of S st dom (f . 0) = E & ( for n being Nat holds f . n is E -measurable ) & dom g = E & ( for x being Element of X st x in E holds
( f # x is convergent & g . x = lim (f # x) ) ) holds
g is E -measurable

let E be Element of S; :: thesis: ( dom (f . 0) = E & ( for n being Nat holds f . n is E -measurable ) & dom g = E & ( for x being Element of X st x in E holds
( f # x is convergent & g . x = lim (f # x) ) ) implies g is E -measurable )

assume that
A1: dom (f . 0) = E and
A2: for n being Nat holds f . n is E -measurable and
A3: dom g = E and
A4: for x being Element of X st x in E holds
( f # x is convergent & g . x = lim (f # x) ) ; :: thesis: g is E -measurable
A5: now :: thesis: for n being Nat holds (Im f) . n is E -measurable
let n be Nat; :: thesis: (Im f) . n is E -measurable
f . n is E -measurable by A2;
then Im (f . n) is E -measurable by MESFUN6C:def 1;
hence (Im f) . n is E -measurable by Th24; :: thesis: verum
end;
A6: dom (Im g) = E by ;
A7: now :: thesis: for x being Element of X st x in E holds
( (Im f) # x is convergent & (Im g) . x = lim ((Im f) # x) )
let x be Element of X; :: thesis: ( x in E implies ( (Im f) # x is convergent & (Im g) . x = lim ((Im f) # x) ) )
assume A8: x in E ; :: thesis: ( (Im f) # x is convergent & (Im g) . x = lim ((Im f) # x) )
then A9: f # x is convergent by A4;
then Im (f # x) is convergent ;
hence (Im f) # x is convergent by A1, A8, Th23; :: thesis: (Im g) . x = lim ((Im f) # x)
g . x = lim (f # x) by A4, A8;
then Im (g . x) = lim (Im (f # x)) by ;
then Im (g . x) = lim ((Im f) # x) by A1, A8, Th23;
hence (Im g) . x = lim ((Im f) # x) by ; :: thesis: verum
end;
dom ((Im f) . 0) = E by ;
then R_EAL (Im g) is E -measurable by A5, A6, A7, Th22;
then A10: Im g is E -measurable by MESFUNC6:def 1;
A11: now :: thesis: for n being Nat holds (Re f) . n is E -measurable
let n be Nat; :: thesis: (Re f) . n is E -measurable
f . n is E -measurable by A2;
then Re (f . n) is E -measurable by MESFUN6C:def 1;
hence (Re f) . n is E -measurable by Th24; :: thesis: verum
end;
A12: dom (Re g) = E by ;
A13: now :: thesis: for x being Element of X st x in E holds
( (Re f) # x is convergent & (Re g) . x = lim ((Re f) # x) )
let x be Element of X; :: thesis: ( x in E implies ( (Re f) # x is convergent & (Re g) . x = lim ((Re f) # x) ) )
assume A14: x in E ; :: thesis: ( (Re f) # x is convergent & (Re g) . x = lim ((Re f) # x) )
then A15: f # x is convergent by A4;
then Re (f # x) is convergent ;
hence (Re f) # x is convergent by ; :: thesis: (Re g) . x = lim ((Re f) # x)
g . x = lim (f # x) by ;
then Re (g . x) = lim (Re (f # x)) by ;
then Re (g . x) = lim ((Re f) # x) by ;
hence (Re g) . x = lim ((Re f) # x) by ; :: thesis: verum
end;
dom ((Re f) . 0) = E by ;
then R_EAL (Re g) is E -measurable by ;
then Re g is E -measurable by MESFUNC6:def 1;
hence g is E -measurable by ; :: thesis: verum